2004
DOI: 10.1007/bf03030641
|View full text |Cite
|
Sign up to set email alerts
|

Changes in antioxidant enzyme activities in detached leaves of cucumber exposed to chilling

Abstract: We studied changes in biochemical and physiological status, level of oxidative damage, and antioxidant enzyme activities in detached leaves of cucumber plants (Cucumis sativus L. cv. Pyunggangnaebyungsamchuk) that were exposed to a low temperature (4~ Chlorophyll fluorescence (Fv/Fm) declined during the chilling treatment, but was slowly restored after the tissues were returned to 25~ Likewise, the fluorescence quenching coefficient and relative water content decreased during the stress period, but then increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…Xia et al showed that ROS is a signaling molecule involved in the response of cucumbers to low-temperature and paraquat stress [ 32 ]. MDA is a product of lipid peroxidation and the extent of membrane damage can be reflected by MDA levels in stressed tissues [ 33 ]. POD can maintain balance by removing excess ROS, which helps plants to endure stress conditions [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al showed that ROS is a signaling molecule involved in the response of cucumbers to low-temperature and paraquat stress [ 32 ]. MDA is a product of lipid peroxidation and the extent of membrane damage can be reflected by MDA levels in stressed tissues [ 33 ]. POD can maintain balance by removing excess ROS, which helps plants to endure stress conditions [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caso isso fosse evidente, tais figuras apresentariam gradientes de concentração ou atividade dos antioxidantes ao longo do período de exposição. O perfil dos antioxidantes não aponta, igualmente, indícios de aclimatação das plantas às condições de exposição da casa de vegetação, o que seria verificado caso os níveis dos mesmos variassem pouco ao longo das amostragens (Barnes et al 1999 (Chaitanya et al 2002, Lee et al 2004, Takac 2004.…”
Section: Discussionunclassified
“…Certamente, alguns fatores de variação devem ser previamente conhecidos para que se tenha certeza da ativação do sistema de respostas antioxidativas em plantas que crescem em ambientes urbanos, pois se sabe que tais defesas variam não somente entre espécies, como também entre plantas da mesma espécie em diferentes estádios de desenvolvimento e entre folhas da mesma planta, em fases distintas de desenvolvimento (Klumpp et al 2000). Além disso, as espécies também respondem às variações ambientais ao longo das estações do ano (Chaitanya et al 2002, Kuk et al 2003, Lee et al 2004, Rivero et al 2004, Zhou & Zhao 2004.…”
Section: Introductionunclassified
“…AOS include superoxide anion (02), the hydroxyl radical ( 9 OH), hydrogen peroxide (H202), and singlet oxygen (102). *Corresponding author; fax +82-55-758-5110 e-mail jjl@gshp.gsnu.ac.kr The increase in AOS, which are also produced during normal aerobic metabolism, seems to occur in response to all abiotic stresses, including chilling (Lee et al, 2004), heavy metal toxicity (Ali et al, 2002), drought (Smirnoff, 1993), and salt Gossett et al, 1996). Failure to quench or inactivate the AOS may lead to the degradation of macromolecules in cells as membrane lipids, proteins, and DNA (EIstner, 1982;Smirnoff, 1993).…”
mentioning
confidence: 98%